STRATEGI GURU SEJARAH DALAM MENGHADAPI TANTANGAN PENDIDIKAN INDONESIA DI ERA SOCIETY 5.0 - Ni Putu Yuniarika Parwati; I Nyoman Bayu Pramartha (Widyadari : Jurnal Pendidikan, 2021)
The current history learning is currently faced with enormous challenges, not yet over with the rolling of the industrial era 4.0, we are again surprised by the emergence of society 5.0 which must be faced and become a separate challenge in the world of education. The formulation of the problem in this study is how the strategy of history teachers in facing the challenges of education in the era of society 5.0. This research uses literature study. In the data collection technique, the writer will explore the data according to the discussion about the challenges of history teachers in facing society 5.0. This study aims to make history teachers increase their competence in the era of society 5.0. The learning strategy of the Society 5.0 era directs teachers to develop their potential and skills with teaching materials, both using information from online media and from the real world. Teachers in teaching methods can keep up with the times with their learning media using technological smells. With these conditions, teachers are challenged to be able to develop their professional competences not only in the conventional learning level, but also in a technology-based learning environment.